2018
DOI: 10.3390/agronomy8100224
|View full text |Cite
|
Sign up to set email alerts
|

Soil Moisture Mapping Using Multi-Frequency and Multi-Coil Electromagnetic Induction Sensors on Managed Podzols

Abstract: Precision agriculture (PA) involves the management of agricultural fields including spatial information of soil properties derived from apparent electrical conductivity (ECa) measurements. While this approach is gaining much attention in agricultural management, farmed podzolic soils are under-represented in the relevant literature. This study: (i) established the relationship between ECa and soil moisture content (SMC) measured using time domain reflectometry (TDR); and (ii) evaluated the estimated SMC with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 58 publications
(76 reference statements)
1
32
0
1
Order By: Relevance
“…Soil moisture is a critical component in land surface-atmospheric processes, and prolonged soil moisture deficits often lead to drought induced vegetation stress [8]. Pasture surface temperature retrieved from thermal infrared (T ir ) provides information about temperature extremes encountered during crop development in this region: extremely low in winter and extremely high in summer, and the consequences on stress and stomatal opening/closure process [19]. In the summer period, especially in the months of July and August, T ir reaches maximum values, while soil moisture has an opposite behaviour.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil moisture is a critical component in land surface-atmospheric processes, and prolonged soil moisture deficits often lead to drought induced vegetation stress [8]. Pasture surface temperature retrieved from thermal infrared (T ir ) provides information about temperature extremes encountered during crop development in this region: extremely low in winter and extremely high in summer, and the consequences on stress and stomatal opening/closure process [19]. In the summer period, especially in the months of July and August, T ir reaches maximum values, while soil moisture has an opposite behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the use of NDVI in pastures [10], these results suggest that NDWI has a more broad application potential, and is appropriate for monitoring drought stress in vegetation, through plant available water (SMC), light-harvesting capacity (biomass) or crop progress and vegetation health (PMC and PQDI, respectively) [19]. The response to the level of SMC and T ir is particularly important, since these parameters are drivers of dryland pasture growth [28].…”
Section: Correlation Between Ndwi and Ndvi Smc T Ir Pasture Moistmentioning
confidence: 99%
“…TDR‐measured θ v in m 3 m −3 (min = 0.1034, max = 0.1798, and median = 0.1298; n = 21) and gravimetrically measured θ v in m 3 m −3 (min = 0.0907, max = 0.1618, and median = 0.1239; n = 21) were within an RMSE of 0.0161 m 3 m −3 (see also Figure ). Average soil bulk density ( n = 28) and the RMSE of θ v estimation ( n = 10) between TDR and gravimetric methods of a shallow soil were 1.31 g cm −3 and 0.018 m 3 m −3 , respectively, in a previous study conducted at the same site (Badewa et al, ). Table compares different TDR criteria used to average θ v measurements at a buried location.…”
Section: Resultsmentioning
confidence: 99%
“…TRIME‐PICO64 TDR probes provide reliable θ v estimations at point scale with an RMSE of 0.016 m 3 m −3 when compared with the gravimetric method. In addition, the TDR measurements are consistent as Badewa et al () reported similar accuracy (RMSE = 0.018 m 3 m −3 ) during the previous growing season at the same location. This accuracy has allowed TRIME‐PICO64 TDR probes (especially in sandy soils) to be used as the reference method of θ v estimation (IMKO Micromodultechnik, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation